THE MANAGEMENT OF NECROTIZING FASCIITIS IN PATIENT WITH SYSTEMIC LUPUS ERYTHEMATOSUS: A CASE REPORT - Israr, Muftihat; Yuza, Abel Tasman; Priyanto, Winarno (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2024)
Introduction: Necrotizing fasciitis due to odontogenic infection is a serious, rapidly progressive infection that infects the skin and soft tissue and has a high mortality rate, requiring early diagnosis and aggressive treatment. Systemic lupus erythematosus is an autoimmune disease that can predispose to severe odontogenic infections, especially necrotizing fasciitis, and worsens immune response to surgical debridement. Case and Management: A 46 years old female patient with a history of systemic lupus erythematosus was referred to the Emergency Department at Hasan Sadikin General Hospital, Bandung with complaints of swelling accompanied by pain at the chin extended to the right lower jaw region. Clinical examination revealed necrosis of the skin, fluctuations, spontaneous drainage, and crepitations. The patient was diagnosed with necrotizing fasciitis and was underwent necrotizing debridement at submental region and tooth extraction under local anesthesia and administration of broad-spectrum empiric antibiotics, followed by wound care with modern dressings. Immunosuppressant drugs were stopped for three days post treatment. Conclusion: Management of necrotizing fasciitis with necrotizing debridement, extraction of teeth, discontinuation of immunosuppressant, and empiric administration of broad-spectrum antibiotics in patients with Systemic Lupus Erythematosus was necessary to prevent further infection to other fascia.